Crystal structures of 4-bromo-2-formyl-1-tosyl-1 H-pyrrole, ( E)-4-bromo-2-(2-nitro-vin-yl)-1-tosyl-1 H-pyrrole and 6-(4-bromo-1-tosyl-pyrrol-2-yl)-4,4-dimethyl-5-nitro-hexan-2-one - Senge, Mathias (My University, 2021)
The crystal structures of three inter-mediate compounds in the synthesis of 8-bromo-2,3,4,5-tetra-hydro-1,3,3-tri-methyl-dipyrrin are reported; 4-bromo-2-formyl-1-tosyl-1H-pyrrole, C12H10BrNO3S, (E)-4-bromo-2-(2-nitro-vin-yl)-1-tosyl-1H-pyrrole, C13H11BrN2O4S, and 6-(4-bromo-1-tosyl-pyrrol-2-yl)-4,4-dimethyl-5-nitro-hexan-2-one, C19H23BrN2O5S. The compounds show multitudinous inter-molecular C-H⋯O inter-actions, with bond distances and angle consistent in the series and within expectations, as well as varied packing types. The merits of collecting data beyond the standard resolution usually reported for small mol-ecules are discussed.
Keywords: Chemical intermediates; Crystal structure; High-resolution; Pyrrole